Printmaking Workshop records - Printmaking Workshop; Robert Hamilton Blackburn Printmaking Workshop Core Collection and Archives (Library of Congress)
Correspondence, subject files, printmaking exhibition files, print listings and catalogs, publicity material, general office files, financial records, photographs, and other records documenting the efforts of the workshop to provide studio space, equipment, instruction, gallery space, and community to artists in printmaking and related fields.
Workshop and artists' cooperative dedicated to teaching and promoting the art of printmaking and related crafts, founded by African-American printmaker Robert Hamilton Blackburn in 1948. Incorporated as the Printmaking Workshop in 1971; dissolved in 2001.
Collection material in English and Spanish.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: Robert Hamilton Blackburn Printmaking Workshop Core Collection and Archives (Library of Congress).
Keywords: Blackburn, Robert Hamilton, -- 1920-; Art, American -- New York (State) -- New York; Artists -- New York (State) -- New York; Artists' studios -- New York (State) -- New York; Arts; Arts -- New York (State) -- New York; Printmakers -- New York (State) -- New York; Prints; Prints -- Technique